Intra- and intermolecular reactivity of organic diacyl systems - Symes, Jillian Ellis (Department of Chemistry, 2016)
The mechanism or a thermal amino group transfer-fragmentation reaction yielding carboxyamides from mixed phosphoric-carboxylic anhydrides (RO(R¹R²N)P(O)OC(O)R³; R = R¹ = alkyl; R² = H, alkyl, aryl; R³ = alkyl, aryl) was elucidated from structure reactivity studies using a model system, R = R¹ = R² = Me, R³ = Ph. Kinetic data was obtained using ¹H nmr spectroscopy; MNDO molecular orbital and molecular mechanics calculations, and the crystal structure or N-methyl-2-benzoyloxy-2-oxo-1, 3, 2-oxazaphosphorinane (Pna2₁; a = 22.229(6)Å, b = 7.597(2)Å, c = 7.210(2)Å; v = 1217.6(6)Å³. Final R = 3. 08% for 1037 reflections with I (rel )> 2αI (rel) and 15 7 parameters) were userul in providing additional in formation about the reaction mechanism .